Histological, Morphometrical and Topographical Study of Sebaceous and Sweat Glands in the Skin of Local Black Males Goat - Sultan, Ghada; Abdulraheem, Muayad (مجلة الانبار للعلوم البيطرية)
The aim of this study was to add more information in the field of knowledge regarding the skin structures of a local black goat. topographical, histological and morphometrical studies were carried out in twelve certain different areas of the skin using twenty healthy adult male goats in the autumn season. Hematoxylin and Eosin stain and Masson's Trichrome stain were used for all samples. Results; that the sebaceous glands are composed of clusters of pale staining epithelial cells that located within the dermis and accompanied all primary and some of the secondary follicles. depending on skin area, the sebaceous glands were large in the skin of muzzle, scrotum, abdomen, the medial surface of the limbs and the abdominal surface of the ear. while their sizes are decreased in the skin of tail, lateral surfaces of limbs and dorsal aspect of ear skin. The size of sebaceous glands were inversely proportional to the hair density. The sweat glands except in the skin tail were apical secretion type, while their levels within the beneath of dermis and their density were varied according to the skin area. the skin of muzzle, tail, dorsal surface of the ear had high glandular density followed by the skin of cranial and middle back in addition to lateral surfaces of limbs. Less glandular density was found in the abdominal surface of ear, abdomen, medial surfaces of limbs and scrotum. In addition to the apocrine sweat glands, serous tubular acinus compound glands in the muzzle skin which extended widely beneath of dermis to subdermal layer. these glands were entirely serious excretion units with the main excretory channel that opens directly on the surface of the skin and had no relation with hair follicles.